PENERAPAN ALGORITMA K-MEANS DALAM MENGATASI PERMASALAHAN SAMPAH (STUDI KASUS: POLA PERILAKU MASYARAKAT DALAM MEMBUANG SAMPAH) - N. Tri Suswanto Saptadi; Vanessa Putri Taga (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2022)
Waste is discharged from a production process both industrial and domestic (household). According to the regulation number 18 of 2008 on waste management, it is mentioned that waste is the rest of the daily activities of humans or natural processes in the form of solid or semi-solid form of organic or inorganic substances. With the factors that cause damage to the environment because of waste, the Government of Makassar City with various shortcomings and challenges and obstacles experienced in handling the waste problem has also been fully aware of this. The local regulation on waste management of Makassar City, referring to the Regional Regulation of Makassar City Number 4 of 2011 on waste management. Classifying patterns of community behavior in disposing of waste to support the work program of the Makassar city government especially the Makassar Environmental Service to deal with waste management and environmental quality monitoring issues. This study aims to assist the Government of Makassar City in making programs to handle waste problems by applying K-Means Algorithm. The results of this study provide information on waste handling that takes place in the city of Makassar and reporting that helps and involves the Government and the City of Makassar's Office of Environment on the handling and management of solid waste regarding services and facilities that have been met.